PRACTICALITY OF TEACHING LEARNING MATERIALS VOCATIONAL SKILLS FOR FACILITIES IN SLB 1 LIMA KAUM - Nella Kusuma (Universitas Yudharta Pasuruan, 2020)
This Development Research aims to develop a teaching material for vocational skills in fashion design designed to enhance student skills, as well as reveal the validity, practicality and effectiveness of the media. This study uses a Research and development development model that focuses on the IDI Method. Data analysis techniques used qualitative data through questionnaires and analyzed statistically. The results obtained from this research and development are as follows: (1) The learning module is a printed module for deaf students in Class X Semester 1 in the Vocational Fashion Dress subject. (2) Practicality of fashion skills skills module for deaf students in Class X Semester 1 based on the teacher's response after going through practicality was declared practical with an average total of 69.6%. (3) Practicality of fashion skills skills modules for deaf students in class X semester 1 based on students' responses after going through practicality was declared practical with an average total of 65%.